Predicting the Intention to Repeated Participation at the Outdoor Event of μτβ-thassos cup from the Destination Image, Activity Involvement and Event Attachment - Polatidou Παναγιώτα; Balaska Παναγιώτα; Polatidou Γεωργία; Alexandris Κωνσταντίνος (Inquiries in Physical Education and Sport, 2012)
The growth of competitive outdoor sport events (trail running, mountain running, triathlon and more) has been rapid in Greece the last five years. The aim of the present study was to explore the role that the destination image (of the island of Thassos), activity involvement (with mountain bike activity) and event attachment (to the “MTbike Thassos Cup” event) can play as predictors of intention to participate again at the event. One hundred and forty three mountain bikers that participated at the 6th MΣΒ-THASSOS CUP, a mountain bike race that was held in the island of Thassos on May 2010, participated at the survey. For the measurement of the destination image Kaplanidou and Vogt (2007) questionnaire was used, for the measurement of involvement the revised by Jun, Kyle and Mowen (2003) involvement questionnaire of McIntyre and Pigram (1992) was used, while for the measurement of event attachment Williams and Vaske’s (2003) questionnaire was used. The results revealed four dimensions for the destination image (infrastructure a=.760, nature α=.825, historic attractions a= .770, affective element a=755), three dimensions for involvement with the mountain bike activity (attraction a=.749, centrality a=.740, self-expression a= .730) and two dimensions for the attachment to the event (event dependence, a=.898 and event identity a=.736). The intention to re-participate at the to the event was predicted by a) the destination image (R2 =.16, F=4.62, p<.005) and specifically the affective dimension (t=-2.45, Beta=.34, p<.05), b) the involvement with the mountain bike activity (R2 =.14, F=6.49, p<.001) and specifically the attraction dimension (t=3.51, Beta=.37, p=.001) and c) the attachment to the event (R2 =.22, F=16.32 p<.001) and specifically the dimension of event identity (t=4.14, Beta=.42, p<.001). The results showed that the emotional dimension developed by visiting a destination, the pleasure that is experienced by engaging in an outdoor activity and the relationship that a participant builds with the outdoor event contributes to his decision to participate at the event again. Organizers can use the above results to motivate participants to return at the event, so that both participants and local communities that host the event can get benefited.